Radiographical Spectrum of High-altitude Pulmonary Edema: A Pictorial Essay - Yanamandra, Uday (Indian J Crit Care Med, 2021)
BACKGROUND: High-altitude pulmonary edema (HAPE) is a common cause of hospitalization in high altitude areas with significant morbidity. The clinical presentation of HAPE can overlap with a broad spectrum of cardiopulmonary diseases. Also, it is associated with varied radiological manifestations mimicking other conditions and often leading to unnecessary and inappropriate treatment. PATIENTS AND METHODS: The primary aim of the study was to study the various radiological manifestations of HAPE through real-world chest radiographs. We present six different chest X-ray patterns of HAPE as a pictorial assay, at initial presentation, and after the resolution of symptoms with supplemental oxygen therapy and bed rest alone. RESULTS: HAPE can present as bilateral symmetrical perihilar opacities, bilateral symmetrical diffuse opacities, unilateral diffuse opacities, bilateral asymmetrical focal opacities, and even lobar consolidation with lower zone or less commonly upper zonal predilection. These presentations can mimic many common conditions like heart failure, acute respiratory distress syndrome, pulmonary embolism, aspiration pneumonitis, pneumonia, malignancy, and tuberculosis. CONCLUSION: A holistic clinical–radiological correlation coupled with analysis of the temporal course can help high-altitude physicians in differentiating true HAPE from its mimics. HOW TO CITE THIS ARTICLE: Yanamandra U, Vardhan V, Saxena P, Singh P, Gupta A, Mulajkar D, et al. Radiographical Spectrum of High-altitude Pulmonary Edema: A Pictorial Essay. Indian J Crit Care Med 2021;25(6):668–674.